ANALISIS TINGKAT KEBISINGAN DI KAWASAN RSUD dr. DORIS SYLVANUS KOTA PALANGKA RAYA - Mei Yuliani; Devia Devia; Murniati Murniati (Jurnal Teknika: Jurnal Teoritis dan Terapan Bidang Keteknikan, 2026)
Increased traffic volume on arterial roads is causing noise in the vicinity of Dr. Doris Sylvanus General Hospital in Palangka Raya, which has the potential to disturb patients. Based on the quality standards of Minister of Environment Decree No. 48 of 1996, the noise threshold for hospitals is set at 55 dB(A). This study aims to analyze noise levels, evaluate the effects of traffic volume and vehicle speed, and formulate control recommendations. The study employed a quantitative descriptive method through field surveys—including a preliminary survey and a main survey—and mathematical modeling conducted in February–March 2026. The collected data included Sound Level Meter (SLM) noise readings, traffic volume, and average vehicle speed. Data analysis was performed by validating the direct measurement results from the Sound Level Meter (SLM) against the results of the Calculation of Road Traffic Noise (CoRTN) model, then comparing them with the quality standards of Ministry of Environment Decree No. 48 of 1996 using descriptive-correlational graphs. The research results show that the average SLM noise levels ranged from 65.6–68.4 dB(A) and the CoRTN model values ranged from 65.2–66.8 dB(A), proving that all observation sessions exceeded the safe threshold of 55 dB(A). Traffic volume was the most significant and dominant factor, with the highest value recorded on Friday afternoon (1,045.4 vehicles per hour; 66.8 dB(A)). Recommended control measures include implementing a one-way traffic system, designing quick drop-off zones, installing concrete walls, and the use of soundproofing materials.